2010
DOI: 10.1590/s0100-06832010000400031
|View full text |Cite
|
Sign up to set email alerts
|

Extração e exportação de nutrientes por variedades de cana-de-açúcar cultivadas sob irrigação plena

Abstract: RESUMOA pesquisa tecnológica para suporte do setor sucroalcooleiro nacional mostra que são esporádicos os trabalhos desenvolvidos com cana-de-açúcar irrigada envolvendo a exigência nutricional. Nesse contexto, objetivou-se quantificar, durante o ciclo de cana-planta de 11 variedades de cana-de-açúcar (SP79-1011, RB813804, RB863129, RB872552, RB943365, RB72454, RB763710, SP78-4764, SP81-3250, RB867515 e RB92579) cultivadas sob irrigação plena, a capacidade de extração e exportação de N, P, K, Ca e Mg, bem como … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
3
31

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 10 publications
9
40
3
31
Order By: Relevance
“…The TCH exhibited an overall mean of 136.08, which is much higher than the yield of 12-month-old plantations in Brazil. Oliveira et al (2010), working with 11 varieties, noted that the variety RB92579, used in the present study, showed highest TCH and highest P use efficiency, which guarantees good representativeness of the results regarding the response of the crop to the treatments.…”
Section: Resultssupporting
confidence: 71%
“…The TCH exhibited an overall mean of 136.08, which is much higher than the yield of 12-month-old plantations in Brazil. Oliveira et al (2010), working with 11 varieties, noted that the variety RB92579, used in the present study, showed highest TCH and highest P use efficiency, which guarantees good representativeness of the results regarding the response of the crop to the treatments.…”
Section: Resultssupporting
confidence: 71%
“…Although the root system of sugarcane is located primarily in the surface layer (0-20 cm), the occurrence of roots in deeper layers is considerable (Battie-Laclau & Laclau, 2009) and promotes the absorption of subsurface mineral N by the plant (Thorburn et al, 2003). The hypothesis that the N mineralization that occurs during the crop development cycle can meet the total N demand of sugarcane plants is supported by the amount of N extracted by sugarcane during the ratoon cycle (from 142 to 179 kg ha -1 ) (Coale et al, 1993;Oliveira et al, 2010). However, it is worth pointing out that the incubation assays for predicting mineralizable N are performed under conditions of controlled humidity, temperature and aeration that are optimal for the soil microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Oliveira et al (2010) a extração de P pela variedade SP79-1011 sob irrigação foi de 25 kg ha -1 de P para produzir 155 Mg de colmos, ou seja, 0,16 kg de P para cada Mg de colmo, resultados que se assemelham às médias obtidas no presente estudo.…”
Section: Resultsunclassified